Exploring the relationship between teacher enjoyment of mathematics, their attitudes towards student struggle and instructional time amongst early years primary teachers. (February 2020) - Russo, James; Bobis, Janette; Sullivan, Peter; Downton, Ann; Livy, Sharyn; McCormick, Melody; Hughes, Sally
Abstract: In this study we explored the relationship between teacher enjoyment of teaching mathematics, their attitudes towards student struggle, and the amount of time teachers spent teaching mathematics. Ninety-eight primary educators were surveyed regarding their attitudes and behaviors towards mathematics instruction. Hierarchical regression analyses revealed that teacher enjoyment of teaching mathematics explained variance in both teacher attitudes towards student struggle and instructional time spent on mathematics, even after relevant educator characteristics were accounted for. Findings suggest that teacher enjoyment of teaching mathematics in the early primary years has important implications for both the quality and quantity of mathematics instruction students receive. Highlights: Enjoyment of teaching mathematics was strongly related to teacher attitudes towards student struggle ( r  = 0.52). Enjoyment of teaching mathematics was related to instructional time spent on mathematics ( r  = 0.25). A reliable measure of teacher attitudes towards student struggle in mathematics was developed (α = 0.74).